Sistematično identificiranje slabo formuliranih anketnih vprašanj - Kogovšek, Tina (Teorija in praksa, 1998)
A lot has been written on question wording and its effects on the responses (e.g. Payne, 1973; Bradburn in Sudman, 1988; Converse in Presser, 1988; Schuman in Presser, 1996). Saris and Gallhofer (1997) summarize the existing classifications of survey questions and up-grade them with a formal lingustic approach. On the basis of the classification it is possible to formulate adequate and qualitative questions according to the aims of a research project. It is also possible to conduct studies about the measurement quality with the same questions as to the contents, but differently formulated. By classifying a sample of public opinion questions from the daily Delo, we attempted to establish, how well and accurately these questions are formulated. On the basis of results of this and some other applications, it can be argued that the mentioned classification system is a very useful tool for establishing the quality of the question wording. However it could be improved at several points.
Keywords: družboslovno raziskovanje; metodologija; ankete; anketna vprašanja; linguistics; lingvistika